Multicentric analysis of the use behavior of cochlear implant users - Oberhoffner, Tobias; Hoppe, Ulrich; Hey, Matthias; Hecker, Dietmar; Bagus, Heike; Voigt, Peter; Schicktanz, Silvia; Braun, Astrid; Hocke, Thomas (Laryngo-Rhino-Otologie, 2018)
INTRODUCTION: Novel cochlear implant speech processors are capable of storing data logs. With the help of this information a more individualized patient care can be provided. However, standard data are missing to a greater extent to the individual usage behavior. MATERIALS AND METHODS: In a retrospective study, the use data of 2687 patients were evaluated. All patients had the Nucleus 6 system from Cochlear Ltd. RESULTS: The data allow a normal range to be defined for the duration of use of cochlear implant speech processors. Likewise, the identification of conspicuous usage behavior is possible.
EVALuna2:35456